Christianity and National Security - Костов, Виктор (Forum Theologicum Sardicense, 2025)
The article addresses the interaction between the Christian faith in post-communist Bulgaria with social and political remnants of extreme suspicion of religion, inherited by the Communist totalitarian regime. Biblical comparisons are drawn for the purpose of illustrating the overarching moral and spiritual importance of the historical period discussed. Religious pluralism is juxtaposed to the doctrine that such variety is a threat to national unity. National security is placed also in the context of human rights, especially freedom of conscience, speech and religion, as these apply to the interaction between the Christian faith and society. Finally, conclusions and recommendations to the church are drawn in the end.